Refugee youth: A deferred hope or an elusive dream? - Dube, Nonhlanhla; Maviza, Gracsious (CGIAR, 2023)
A protracted refugee situation refers to a scenario when an entire generation of a family spend their whole lives in refugee camps. In this blog post, we reflect on the recent fieldwork we conducted at the Tongogara Refugee Camp in Zimbabwe. The majority of the people we interviewed in the camp have been residing there for 10 to 25 years, with some even born there.